Regenerative and Innovative Utilization of Coffee Residue and Waste Cooking Oil: Improving Rheological Properties of Recycled Asphalt - Ruipeng Zhu; Chunhua Hu (Buildings)
Currently, there is limited research on the utilization of spent coffee grounds (SCG) in asphalt pavement. This study explores using SCG as a novel rejuvenator together with waste cooking oil (WCO) to enhance the performance of aged asphalt (AA). The high-temperature performance of recycled asphalt was preserved using SCG containing oily components. However, the low-temperature performance of long-term aged asphalt could not be completely restored to the level of virgin asphalt. Therefore, various dosages of SCG and WCO were utilized to optimize the recovery of low-temperature properties while maintaining high-temperature performance. The recycled asphalt (RA) was analyzed through conventional indexes, microscopic characteristics, and rheological properties using penetration and softening point tests, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and a dynamic shear rheometer (DSR). The results showed that the G* of W7S12 increased by 90% relative to virgin asphalt. Additionally, at strain levels of 2.5% and 5%, the fatigue life of W8S18 was approximately 3.39 times and 2.34 times greater, respectively, than that of the virgin asphalt. The addition of a rejuvenator can enhance the low-temperature cracking resistance of aged asphalt. Moreover, the FTIR results indicated that the regeneration mechanism of recycled asphalt consisted of physical blending. In summary, W7S12 exhibited the highest high-temperature performance, while W8S18 demonstrated superior fatigue life. This study may promote the sustainable development of asphalt pavements by utilizing organic waste as a rejuvenator through resource recovery.